2023
DOI: 10.1088/1758-5090/acfe3b
|View full text |Cite
|
Sign up to set email alerts
|

On the reproducibility of extrusion-based bioprinting: round robin study on standardization in the field

David Grijalva Garces,
Svenja Strauß,
Sarah Gretzinger
et al.

Abstract: The outcome of three-dimensional (3D) bioprinting heavily depends, amongst others, on the interaction between the developed bioink, the printing process, and the printing equipment. However, if this interplay is ensured, bioprinting promises unmatched possibilities in the health care area. To pave the way for comparing newly developed biomaterials, clinical studies, and medical applications (i.e. printed organs, patient-specific tissues), there is a great need for standardization of manufacturing methods in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…An example is the round-robin study conducted by Garces et al, which involved 15 international groups. The aim was to analyze reproducibility and introduce standards to the bioprinting field in order to accelerate the transition from laboratory practice to production for clinical applications 34 . They concluded that automated image analysis (IA) is a suitable tool for assessing printing process reproducibility, but quantitative comparability in the bioprinting field has not yet been achieved due to lack of standardization in terms of bioprinting equipment.…”
Section: Discussionmentioning
confidence: 99%
“…An example is the round-robin study conducted by Garces et al, which involved 15 international groups. The aim was to analyze reproducibility and introduce standards to the bioprinting field in order to accelerate the transition from laboratory practice to production for clinical applications 34 . They concluded that automated image analysis (IA) is a suitable tool for assessing printing process reproducibility, but quantitative comparability in the bioprinting field has not yet been achieved due to lack of standardization in terms of bioprinting equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the digital nature of 3D printing ensures reproducibility, allowing for the consistent manufacture of bioremediation devices across different locations ( Thompson et al, 2016 ). Recent research has identified key factors that can be improved to enhance the reproducibility and reliability of bioprinting, which holds great potential for future applications ( Grijalva Garces et al, 2024 ).…”
Section: Considerations Of 3d Printing In Bioremediationmentioning
confidence: 99%
“…On the other hand, MEW removes the buckling instabilities present in SES, greatly improving the reproducibility of desired geometries [ 130,134,135 ] with even less engineering effort than most customized SES setups would require. [ 135 ] Enhancing the stability of SES to be more independent of fiber placement and atmospheric conditions [ 136–138 ] is integral for medical device manufacturing, [ 139 ] which melt‐based systems demonstrate to be less affected by. [ 140,141 ] MEW being a stable process holds especially true for the fabrication of micro‐sized, porous structures with highly defined architecture and hierarchy in both, the planar and tubular category and beyond.…”
Section: The Future Of Tubular Melt Electrowriting For Biomimetic Vas...mentioning
confidence: 99%